Measurements of dispersion of ultrasonic wave velocity in thin layers by the ultrasonic spectroscopy - WOJDOWSKI, W. (Archives of Acoustics, 1992)
This paper presents the results of measurements of the phase velocity dispersion of ultrasonic waves in thin aluminium sheets. The interaction between ultrasonic waves and a thin solid layer is analysed and the theoretical relations for the transmission and reflection coefficients are presented. Experiments are based on the spectrum analysis of ultrasonic pulses, generated by the broad-band probes in the frequency range of 2-13 MHz. From the maxima of transmission coefficients for different incidence angles the phase velocity of Lamb waves is determined as a function of ultrasonic wave frequency. Presented method allows to determine the acoustic parameters and the dispersion curves for the velocity of Lamb waves in thin layers.